KAJIAN ETNOBOTANI FAMILI RUBIACEAE OLEH MASYARAKAT KOTA TARAKAN DAN POTENSINYA SEBAGAI SUMBER BELAJAR BIOLOGI - Nur Amira Haris; Anifah Toding (Biopedagogia, 2020)
The research have a goal to identify species of Rubiaceae that is used in Tarakan community. Collecting data used participatory rural appraisal, and was used open-interview to 30 informants. The result showed 8 species of Rubiaceae that is used by Tarakan community.  In general, Rubiaceae was used as a food sources and medicine. The result can be used as a complementary content in Ethnobotany course. Keywords: Rubiaceae, Tarakan